The (In)visibility of Misdiagnosis in Point-of-Care HIV Testing in Zimbabwe. Issue 4 (19th May 2022) - Skovdal, Morten; Beckmann, Nadine; Maswera, Rufurwokuda; Nyamukapa, Constance; Gregson, Simon
ABSTRACT: There is a global trend to introduce point-of-care diagnostic tests, enabling healthcare workers at any level to test, provide results, and initiate immediate treatment if necessary. This article explores how healthcare workers conducting rapid HIV tests – in contexts of limited external quality assurance mechanisms – ascertain the accuracy of their test results. Drawing on interview data and participant observations from health facilities in Zimbabwe, we open the black box of misdiagnosis (in)visibility and reveal a range of proxies and markers that HIV testers draw on to develop certainty, or question, the reliability of their diagnostic classifications.